(untitled) (AL MUNAZHZHARAH, 2019)
In Balearjo Village, Gondanglegi Subdistrict, Malang Regency at present, almost most of the people choose to go abroad to become Indonesian Workers (TKI) as an effort to fulfill their family’s living needs. Although the beginning of the departure of his wife to be a TKW was approved by both of them, but the impact affected the reasons for his marriage to divorce. This research is included in the case study category. While this type of research based on its nature this study is categorized as descriptive research. Through data collection using interviews, observations, and documentation, it is obtained exposure to data and research findings that ultimately can be made discussion that leads to answers from the focus of research. The results of the study stated that the number of divorces that occurred in the family of Women Workers (TKW) abroad in Balearjo Village Gondanglegi District Malang Regency was due to the overflowing biological needs of the husband which ultimately impacted on alternative choices taken by the husbands who were left working by his wife as a Female Worker (TKW) abroad, which has another ideal woman (WIL).